Board of Directors Structure and Firm Performance: Evidence from Indonesia and Malaysia - Fajarwati, Elisa; Witiastuti, Rini Setyo (Universitas Negeri Semarang, 2022)
The purpose of this study is to identify the influence of board size, independent director, board meeting frequency and women director on firm performance. Type of this research is a quantitative research using secondary data. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange and Bursa Malaysia in 2015-2019. The sampling method used was purposive sampling consisting of 120 companies in Indonesia Stock Exchange and 209 companies in Bursa Malaysia. The data analysis method used is multiple regression analysis which is preceded by the selection of a panel data estimation model using the Eviews 9 software. The results of the model test show that the best panel data estimation model is using the random effect model. The results showed that board size and board meeting frequency have a significant positive effect on the performance of manufacturing companies in Indonesia Stock Exchange and Bursa Malaysia. Independent directors has a significant positive effect on firm performance in Bursa Malaysia, but have a significant negative effect on firm performance in Indonesia Stock Exchange. Women directors has a significant positive effect on firm performance in Indonesia Stock Exchange, but has significant negative effect on firm performance in Bursa Malaysia.